High-flexibility MOF (Metal Organic Framework) composite membrane as well as preparation method and application thereof

By depositing the AgNWs@MOF seed layer on the flexible polymer base layer and preparing the MOF film layer by using the secondary growth method, the problems of difficult and poor flexibility in the preparation of the existing MOF film are solved, and high flexibility and high performance CO2 are achieved /N2 separation membrane.

CN119386686AActive Publication Date: 2025-02-07BEIJING INST OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411881776.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-07
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Most of the existing MOF films are prepared on rigid inorganic substrates, which have problems such as difficult preparation and poor processing flexibility, making it difficult to prepare a high-flexible and high-performance CO2/N2 separation membrane.

Method used

AgNWs@MOF seed layer connection between the flexible polymer base layer and the MOF film layer was used to prepare a highly flexible MOF composite film by vacuum-assisted self-assembly and secondary growth method.

Benefits of technology

The interface bonding force between the MOF film and the polymer substrate is improved, the stability and selectivity of the membrane structure are enhanced, and the difficulty of film amplification is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386686A_ABST
    Figure CN119386686A_ABST
Patent Text Reader

Abstract

The invention relates to a high-flexibility MOF (Metal Organic Framework) composite film as well as a preparation method and application thereof. The high-flexibility MOF composite film comprises a flexible polymer substrate layer and an MOF film layer positioned above the flexible polymer substrate layer, the flexible polymer substrate layer and the MOF film layer are connected through an AgNWs (at) MOF crystal seed layer deposited on the flexible polymer substrate layer; the AgNWs (at) MOF is of a core-shell structure formed by wrapping one-dimensional silver nanowires with MOF, and the AgNWs (at) MOF seed crystal layer is of a fiber net structure formed by the core-shell structure. The one-dimensional silver nanowire is used as an MOF seed carrier, and the high-flexibility MOF composite film is prepared through vacuum-assisted self-assembly, secondary growth and a functional polymer spin-coating strategy, so that the interface bonding force between the MOF film and a polymer substrate is effectively improved, and the structural stability of the film is enhanced. Meanwhile, the crystallinity of the MOF film is improved by the secondary growth method, and intercrystalline defects are reduced, so that the selectivity of the film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas separation, and in particular to a highly flexible MOF composite membrane and a preparation method and application thereof. Background Art

[0002] As one of the main greenhouse gases, excessive emissions of carbon dioxide (CO2) have had a serious impact on the ecological environment, leading to global warming, rising sea levels, and frequent extreme weather events. Carbon capture, utilization, and storage (CCUS) technology is one of the key technologies for reducing carbon dioxide emissions, among which efficient carbon capture technology is the premise and basis for reducing carbon emissions and further conversion and utilization of CO2. At present, the mature CO2 capture technologies in industrial applications mainly include physical adsorption, chemical absorption, and membrane separation technology. However, physical adsorption technology requires adsorbent regeneration, and has low adsorption capacity and selectivity; while chemical absorption technology has problems such as high energy consumption and high equipment corrosion. Compared with the above traditional technologies, the new membrane separation technology has the advantages of low energy consumption, small footprint, and applicability to various processing scales, and has great application potential in the field of CO2 separation. However, the existing membrane materials generally have a trade-off effect between permeability and selectivity, which limits their industrial application. Therefore, it is urgent to develop high-performance CO2 separation membrane materials to improve the market competitiveness of membrane carbon capture.

[0003] Metal organic framework (MOF) materials have the characteristics of high porosity, adjustable pore size, functionalized topological structure, etc., and are considered to be one of the most promising materials for preparing high-performance CO2 separation membranes. Hou et al. prepared ZIF-7-8 membranes on anodized aluminum substrates by fast current driven synthesis (FCDS), which have excellent separation performance for CO2 / N2 binary mixtures (Angew.Chem.Int.Ed.2019,58,327-331). Zhang et al. prepared highly oriented ZIF-8 membranes on anodized aluminum substrates by secondary growth method, which have good CO2 / N2 separation performance (J.Membr.Sci.2022,641,119915). Patent CN202110544809.0 discloses a method for preparing MOF membranes on inorganic substrates by crystal-assisted supercritical fluid technology and its application in gas separation.

[0004] The above research has made positive contributions to the preparation and application development of MOF membranes for CO2 / N2 separation. However, most of these MOF membranes are prepared on rigid inorganic substrates, and there are technical bottlenecks such as difficulty in membrane scale-up preparation and poor flexibility in membrane assembly processing and manufacturing. Polymer microporous membranes have the advantages of high mechanical strength and easy expansion, and have been widely used as substrates for pervaporation, nanofiltration, and reverse osmosis membrane materials. However, due to the significant differences in the physicochemical properties of the two, it is still a huge challenge to prepare ultra-thin and defect-free MOF membranes with continuous transmission channels (high permeability) and high symbiosis (high selectivity) on flexible polymer substrates. Therefore, the development of a simple and effective method for preparing highly flexible MOF membranes has important research significance and application value. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the present invention develops a highly flexible MOF composite membrane and a preparation method thereof for efficient CO2 / N2 separation.

[0006] The present invention is specifically implemented through the following solutions:

[0007] A highly flexible MOF composite membrane, comprising:

[0008] A flexible polymer substrate layer and a MOF film layer located above the flexible polymer substrate layer;

[0009] The flexible polymer substrate layer and the MOF film layer are connected by an AgNWs@MOF seed layer deposited on the flexible polymer substrate layer; the AgNWs@MOF is a core-shell structure formed by MOF wrapping one-dimensional silver nanowires, and the AgNWs@MOF seed layer is a fiber mesh structure formed by the core-shell structure.

[0010] Furthermore, the relationship between the deposition amount of the AgNWs@MOF seed layer and the area of ​​the flexible polymer substrate layer is 0.1-0.6 g / m 2 .

[0011] Specifically, the above-mentioned area should be understood as the surface area where the deposition behavior occurs.

[0012] Furthermore, the flexible polymer substrate layer is a polymer microporous base membrane, specifically including one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyethylene (PE) or polypropylene (PP).

[0013] Preferably, the polymer microporous base membrane is in the shape of a flat plate, a tubular or a hollow fiber.

[0014] Furthermore, the MOF includes ZIF-8, ZIF-67, ZIF-71, ZIF-7 or ZIF-62.

[0015] Furthermore, a functional polymer layer is also included above the MOF membrane layer, and the functional polymer is one or more of Pebax1657, Pebax 2533, Pebax 4033, and Pebax 5533.

[0016] The present invention also provides a method for preparing a highly flexible MOF composite membrane, comprising the following steps:

[0017] S1) mixing the one-dimensional silver nanowire, the metal ion solution of the MOF and the organic ligand solution of the MOF to prepare AgNWs@MOF;

[0018] S2) depositing the AgNWs@MOF on the flexible polymer substrate layer by a vacuum-assisted self-assembly method to form an AgNWs@MOF seed layer to obtain a first composite film;

[0019] S3) placing the first composite film in a mixed solution of metal ions and organic ligands of the MOF, growing a MOF film layer on the AgNWs@MOF seed layer, and obtaining the highly flexible MOF composite film.

[0020] The present invention also provides another method for preparing a highly flexible MOF composite membrane, characterized in that it comprises the following steps:

[0021] S1) mixing the one-dimensional silver nanowires, the metal ion solution of the MOF and the organic ligand solution of the MOF to prepare AgNWs@MOF;

[0022] S2) depositing the AgNWs@MOF on the flexible polymer substrate layer by a vacuum-assisted self-assembly method to form an AgNWs@MOF seed layer to obtain a first composite film;

[0023] S3) placing the first composite film in a mixed solution of metal ions and organic ligands of the MOF, growing a MOF film layer on the AgNWs@MOF seed layer, and obtaining a second composite film;

[0024] S4) spin coating the functional polymer on the MOF film layer of the second composite film to obtain the highly flexible MOF composite film.

[0025] Furthermore, step S1) further includes mixing the one-dimensional silver nanowires, the metal ion solution of the MOF and the organic ligand solution of the MOF, and after the reaction is completed, centrifuging, washing and drying to obtain AgNWs@MOF.

[0026] Furthermore, the one-dimensional silver nanowires in step S1) are obtained by the following method:

[0027] Silver salt, polyvinyl pyrrolidone and halide are dissolved in liquid polyhydroxy alcohol, mixed evenly, and then subjected to microwave solvent thermal synthesis reaction to obtain a suspension, which is then centrifuged, washed and dried to obtain the one-dimensional silver nanowire.

[0028] Specifically, the silver salt is selected from one or more of silver nitrate, silver sulfate and silver chloride. The liquid polyhydric alcohol is selected from one or more of ethylene glycol, propylene glycol, glycerol and polyethylene glycol, preferably ethylene glycol; the halide is selected from one or more of sodium chloride, potassium chloride, ammonium chloride, magnesium chloride, zinc chloride, ferric chloride, cupric chloride, sodium bromide, potassium bromide, cupric bromide, sodium iodide and potassium iodide.

[0029] Specifically, the molar ratio of the polyvinyl pyrrolidone to the silver ions in the silver salt is 1:3-10; the molar ratio of the halogen ions in the halide to the silver ions in the silver salt is 1:1-200.

[0030] Specifically, the microwave solvent thermal synthesis reaction time is 0.5 to 3 hours, the reaction temperature is 150 to 250° C., and the power is 800 to 1500W.

[0031] Furthermore, in step S1), the molar ratio of the metal ion to the organic ligand is 1:1-10; and in step S3), the molar ratio of the metal ion to the organic ligand in the mixed solution is 1:20-100.

[0032] Specifically, in step S1), the metal ion solution of the MOF and the organic ligand solution of the MOF both use methanol as solvent; in step S3), the mixed solution uses water as solvent.

[0033] Furthermore, the metal ions and organic ligands of the MOF in step S1) are the same as those in step S3).

[0034] Specifically, in step S1) and step S3), the metal ions of the MOF are made of metal salts as raw materials, including any one or more of zinc nitrate, zinc chloride, zinc acetate, cobalt nitrate, cobalt chloride, and cobalt acetate.

[0035] Specifically, in step S1) and step S3), the organic ligand of the MOF includes one or more of imidazole, 2-methylimidazole, 2-vinylimidazole, benzimidazole, 4,5-dichloroimidazole, and imidazole-2-carboxaldehyde.

[0036] Preferably, in some embodiments, in step S1), the organic ligand of MOF is dissolved in methanol, and then the AgNWs are added and ultrasonically dispersed to obtain a first mixed solution; the metal salt is dissolved in methanol to obtain a second mixed solution; the first mixed solution and the second mixed solution are quickly mixed and stirred for reaction for 0.1 to 2 hours at a reaction temperature of 20 to 60°C, and the mixture is centrifuged, washed, and dried to obtain AgNWs@MOF seed crystals.

[0037] Preferably, in step S3), an aqueous solution of a metal salt and an aqueous solution of an organic ligand are prepared respectively, and after being mixed evenly, a mixed solution of metal ions and organic ligands of the MOF is obtained, and the first composite membrane is placed in the mixed solution for secondary growth of a MOF membrane layer, and the reaction is carried out for 2 to 10 hours at a reaction temperature of 20 to 60° C. After the reaction is completed, the membrane is fully rinsed with deionized water and methanol, and dried to obtain the highly flexible MOF composite membrane or the second composite membrane.

[0038] Preferably, the first composite membrane is vertically placed in a mixed solution of metal ions and organic ligands of the MOF to secondary grow a MOF membrane layer, which can prevent MOF crystals generated in the solution from adhering to the first composite membrane, thereby making it difficult to clean later.

[0039] Preferably, the undeposited surface of the first composite membrane away from the AgNWs@MOF seed layer is subjected to wall adhesion or other treatments so that the undeposited surface will not grow a MOF membrane layer for the second time, thereby preventing the MOF membrane layers grown on both sides from clogging the pores of the polymer microporous substrate and increasing the gas mass transfer resistance.

[0040] Preferably, in step S2), the AgNWs@MOF is dispersed in a methanol solution, and one-dimensional AgNWs@MOF is deposited on the flexible polymer substrate layer by vacuum-assisted self-assembly, and then dried at room temperature to obtain a first composite film.

[0041] Preferably, in step S4), the functional polymer is dissolved in ethanol to obtain a casting solution; preferably, the dissolution is carried out at 70 to 90° C.; preferably, the mass fraction of the functional polymer is 3 to 10 wt %.

[0042] Preferably, in step S4), the casting solution is spin-coated onto the MOF film layer of the second composite film. Preferably, the spin-coating rate is 200 to 2000 rpm, and the number of spin-coatings is 1 to 5 times; preferably, after spin-coating, the film is dried at 50 to 80° C. for 12 to 24 hours to obtain a highly flexible MOF composite film.

[0043] The present invention also provides an application of a highly flexible MOF composite membrane in CO2 / N2 gas separation.

[0044] Beneficial effects:

[0045] 1. Using one-dimensional silver nanowires (AgNWs) as MOF seed carriers, and through vacuum-assisted self-assembly, secondary growth and functional polymer spin coating strategies, a highly flexible MOF composite membrane was prepared, which effectively improved the interfacial bonding between the MOF membrane and the polymer substrate and enhanced the stability of the membrane structure. At the same time, the secondary growth method improved the crystallinity of the MOF membrane and reduced intercrystalline defects, thereby improving the selectivity of the membrane.

[0046] 2. Using AgNWs@MOF arranged in a fiber mesh as seeds, the highly symbiotic MOF was induced through in situ secondary growth, and a continuous transfer channel for the molecules to be separated was constructed in the MOF membrane, which reduced the diffusion resistance of the target molecules, enhanced the mass transfer process of the molecules in the membrane, and improved the membrane selectivity and permeability.

[0047] 3. Through the polymer spin coating strategy, the MOF intercrystalline defects were effectively repaired, the stability and mechanical strength of the MOF membrane were improved, the gas separation performance was further improved and the difficulty of membrane scale-up preparation was reduced.

[0048] 4. This invention uses one-dimensional silver nanowires as seed carriers for the first time, and prepares highly flexible MOF composite membranes through secondary growth assisted by polymer spin coating strategy, providing high-performance membrane materials for the field of gas separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is the SEM image of AgNWs obtained in step 1) of Example 3;

[0050] Figure 2 This is the SEM image of AgNWs@ZIF-8 obtained in step 2) of Example 3;

[0051] Figure 3 The SEM image of the surface of the ZIF-8 membrane in the second composite membrane obtained in step 4) of Example 3;

[0052] Figure 4 is a SEM image of a cross section of the second composite membrane obtained in step 4) of Example 3;

[0053] Figure 5 The surface SEM image of the Pebax-ZIF-8-AgNWs@ZIF-8-PAN composite film obtained in step 5) of Example 3;

[0054] Figure 6 This is a comparison result diagram of the CO2 / N2 separation performance of the Pebax-ZIF-8-AgNWs@ZIF-8-PAN composite membrane obtained in Examples 1-4;

[0055] Figure 7This is a comparison result of the CO2 / N2 separation performance of the Pebax-ZIF-8-AgNWs@ZIF-8-PAN composite membrane obtained in Example 3 and the membrane materials prepared in Comparative Examples 1-3;

[0056] Figure 8 The stress-strain curves of the PAN film and the Pebax-ZIF-8-AgNWs@ZIF-8-PAN composite film obtained in Examples 1-4;

[0057] Fig. 9 This is the bending test of the Pebax-ZIF-8-AgNWs@ZIF-8-PAN composite film obtained in Example 3 and the surface SEM image after bending. DETAILED DESCRIPTION

[0058] The content of the present invention is further described below in conjunction with the accompanying drawings, embodiments and comparative examples, but the scope of protection claimed by the present invention is not limited to the following embodiments.

[0059] Embodiment 1:

[0060] 1) Prepare 30 mL of 0.47 g / mL PVP ethylene glycol solution, then add 0.06 mmol of sodium chloride to the solution and fully dissolve to obtain solution 1. Dissolve silver nitrate in ethylene glycol to obtain 50 mL of 0.06 mol / L solution 2. Add solution 1 dropwise to solution 2, stir evenly, and transfer the obtained mixture to a microwave reactor, and react at 160° C. and 1000 W for 1 hour. Centrifuge the obtained suspension, wash with methanol, and dry to obtain the AgNWs.

[0061] 2) 20 mL of a 0.5 mol / L dimethyl imidazole methanol solution was prepared, and then 20 mg of the AgNWs was added and ultrasonically dispersed to obtain solution 3; 12 mL of a 0.1 mol / L zinc nitrate hexahydrate methanol solution was prepared to obtain solution 4. The solution 3 and solution 4 were mixed and stirred for 1 h, washed with methanol and dried to obtain AgNWs@ZIF-8.

[0062] 3) The AgNWs@ZIF-8 was dispersed in a methanol solution, and a flat polyacrylonitrile polymer film (PAN film) was used as a substrate. One-dimensional AgNWs@ZIF-8 was deposited on one surface of the PAN film by vacuum-assisted self-assembly, with a deposition amount of 0.1 g / m 2 , and allowed to stand and dry at room temperature to obtain a first composite film.

[0063] 4) Prepare 200 mL of 0.018 mol / L zinc nitrate hexahydrate aqueous solution and 200 mL of 1.28 mol / L dimethylimidazole aqueous solution respectively and mix them evenly. The undeposited surface of the first composite film away from the AgNWs@MOF seed layer is attached to the wall and placed vertically in the above mixed solution, reacted at 25°C for 6 hours, and a ZIF-8 layer is prepared by secondary growth, fully rinsed with deionized water and methanol, and then dried at room temperature to obtain a second composite film.

[0064] 5) 50 g of 5 wt% Pebax 1657 ethanol solution was spin coated on the surface of the second composite film three times at 600 rpm. The prepared film was dried at 60° C. for 12 h to obtain a highly flexible Pebax-ZIF-8-AgNWs@ZIF-8-PAN composite film.

[0065] Embodiment 2:

[0066] The only difference between Example 1 and Example 1 is that in step 3), the deposition amount of AgNWs@ZIF-8 is 0.2 g / m 2 .

[0067] Embodiment 3:

[0068] The only difference between Example 1 and Example 1 is that in step 3), the deposition amount of AgNWs@ZIF-8 is 0.4 g / m 2 .

[0069] Embodiment 4:

[0070] The only difference between Example 3 and Example 3 is that in step 3), the deposition amount of AgNWs@ZIF-8 is 0.6 g / m 2 .

[0071] Comparative Example 1:

[0072] The only difference between Example 3 and Example 3 is that step 2) of Example 3 is not included, and AgNWs are directly deposited on the PAN substrate to obtain a Pebax-ZIF-8-AgNWs-PAN composite film.

[0073] Comparative Example 2:

[0074] The only difference between Example 3 and Example 3 is that: Step 1) to Step 3) of Example 3 are not included, and the ZIF-8 membrane is directly grown on the PAN substrate to obtain the Pebax-ZIF-8-PAN composite membrane.

[0075] Comparative Example 3:

[0076] The only difference between Example 3 and Example 3 is that: Step 1) to Step 4) of Example 3 are not included, and Pebax1657 is directly spin-coated on the PAN substrate to obtain a Pebax-PAN composite film.

[0077] Performance Test:

[0078] The membrane materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were passed through a gas separation device to test their CO2 / N2 separation performance. The results are as follows: Figure 6 The specific test standards are as follows:

[0079] The test area is 25cm 2 , the temperature is 25℃, the test gas is a mixture of CO2 / N2 (15:85), the pressure is maintained at 0.1MPa, Ar is the carrier gas, and the permeability (P) and separation factor (α) are calculated by the following formula:

[0080]

[0081] Among them, N i is the permeation rate of component i (mol / s), ΔP i is the transmembrane partial pressure (Pa). A is the effective area of ​​the membrane (m 2 ). X and Y are the mole fractions of components i and j in the feed and permeate, respectively.

[0082] Depend on Figure 6 It can be seen that in Examples 1-4, one-dimensional AgNWs@ZIF-8 was used as a seed crystal, and a high-performance flexible MOF composite membrane was obtained through secondary growth, and the addition of one-dimensional AgNWs@ZIF-8 seeds in step 3) greatly contributed to the improvement of the separation performance of the membrane. By changing the deposition amount of one-dimensional AgNWs@ZIF-8 seeds in step 3), the permeation rate of CO2 was 995-1264 Barrer, and the CO2 / N2 selectivity was 37-45, of which the deposition amount of one-dimensional AgNWs@ZIF-8 was 0.4 g / m 2 When , the CO2 / N2 separation performance reaches the highest, the permeation rate reaches 1264 Barrer and the selectivity is 45. Figure 7 It shows that a high-performance flexible MOF composite membrane was prepared by secondary growth using one-dimensional AgNWs@ZIF-8 as the seed, and its separation factor and permeation flux were much higher than those of the membrane materials prepared in Comparative Examples 1-3.

[0083] The mechanical properties of the PAN-based membrane and the membrane materials of Examples 1-4 were tested. The membrane materials were mounted on the fixture of a universal tensile machine and the tensile rate was set to 10 mm / min for testing. The results are as follows: Figure 8The stress-strain curves show that the presence of silver nanowires increases the maximum tensile stress and tensile strength of the prepared flexible ZIF-8 film, and the maximum tensile stress increases and the tensile strength decreases with the increase of the amount of seed deposition.

[0084] like Fig. 9 As shown, the high-flexibility Pebax-ZIF-8-AgNWs@ZIF-8-PAN composite membrane obtained in Example 3 was subjected to 90° and 180° bending tests, and was repeatedly bent 20 times at 90° and 180° respectively. The electron microscope image of the composite membrane finally obtained showed that there was no obvious change on the membrane surface, further proving that the composite membrane obtained in the present application has high flexibility.

[0085] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A highly flexible MOF composite membrane, characterized in that: include: A flexible polymer substrate layer and a MOF film layer located above the flexible polymer substrate layer; The flexible polymer substrate layer and the MOF film layer are connected by an AgNWs@MOF seed layer deposited on the flexible polymer substrate layer; the AgNWs@MOF is a core-shell structure formed by MOF wrapping one-dimensional silver nanowires, and the AgNWs@MOF seed layer is a fiber mesh structure formed by the core-shell structure.

2. The highly flexible MOF composite membrane according to claim 1, characterized in that: The relationship between the deposition amount of the AgNWs@MOF seed layer and the area of ​​the flexible polymer substrate layer is 0.1-0.6 g / m 2 .

3. The highly flexible MOF composite membrane according to claim 1, characterized in that: The flexible polymer substrate layer includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyethylene or polypropylene.

4. The highly flexible MOF composite membrane according to claim 1, characterized in that: The MOF includes ZIF-8, ZIF-67, ZIF-71, ZIF-7 or ZIF-62.

5. The highly flexible MOF composite membrane according to claim 1, characterized in that: A functional polymer layer is also provided above the MOF membrane layer, and the functional polymer is one or more of Pebax 1657, Pebax 2533, Pebax 4033, and Pebax 5533.

6. A method for preparing a highly flexible MOF composite membrane according to any one of claims 1 to 4, characterized in that: The steps include: S1) mixing the one-dimensional silver nanowires, the metal ion solution of the MOF and the organic ligand solution of the MOF to prepare AgNWs@MOF; S2) depositing the AgNWs@MOF on the flexible polymer substrate layer by a vacuum-assisted self-assembly method to form an AgNWs@MOF seed layer to obtain a first composite film; S3) placing the first composite film in a mixed solution of metal ions and organic ligands of the MOF, growing a MOF film layer on the AgNWs@MOF seed layer, and obtaining the highly flexible MOF composite film.

7. A method for preparing a highly flexible MOF composite membrane according to claim 5, characterized in that: The steps include: S1) mixing the one-dimensional silver nanowires, the metal ion solution of the MOF and the organic ligand solution of the MOF to prepare AgNWs@MOF; S2) depositing the AgNWs@MOF on the flexible polymer substrate layer by a vacuum-assisted self-assembly method to form an AgNWs@MOF seed layer to obtain a first composite film; S3) placing the first composite film in a mixed solution of metal ions and organic ligands of the MOF, growing a MOF film layer on the AgNWs@MOF seed layer, and obtaining a second composite film; S4) spin coating the functional polymer on the MOF film layer of the second composite film to obtain the highly flexible MOF composite film.

8. The preparation method according to claim 6 or 7, characterized in that: The one-dimensional silver nanowires in step S1) are obtained by the following method: Silver salt, polyvinyl pyrrolidone and halide are dissolved in liquid polyhydroxy alcohol, mixed evenly, and then subjected to microwave solvent thermal synthesis reaction to obtain a suspension, which is then centrifugally washed and dried to obtain the one-dimensional silver nanowire.

9. The preparation method according to claim 6 or 7, characterized in that: The molar ratio of the metal ion to the organic ligand in step S1) is 1:1-10; the molar ratio of the metal ion to the organic ligand in the mixed solution in step S3) is 1:20-100.

10. Use of the highly flexible MOF composite membrane according to any one of claims 1 to 5 in CO2 / N2 gas separation.

Citation Information

Patent Citations

  • A method for preparing MOF membranes using seed-assisted supercritical technology and its application in gas separation.

    CN113413778B

  • Method for preparing metal organic framework film by using hydroxide nanowires and organic ligands

    CN102872728A

  • Method for preparing metal organic frame gas separating film by utilizing pinning effect of metal organic nano rod array on macro-pore substrate

    CN103566779A

  • Preparation method for forming metal organic framework ZIF-67 film by utilizing cobalt nano array layer conversion

    CN105233702A

  • Visible light response type titanium dioxide nano-wire / metal organic framework / carbon nano-fiber membrane as well as preparation method and application thereof

    CN108772108A